The Effect of Memory Card Game on Pupils’ English Vocabulary at Primary School - Yasminar Amaerita Telaumbanua; April Niwati Gea; Annisa Fitri Harefa; Icha Muliyanti Telaumbanua; Crystian Akbar Maulana; Ideal Nat Firman Laia; Merihati Buulolo (Universitas Nusantara PGRI Kediri, 2026)
The purpose of this study was to investigate the effect of a Memory Card Game on the English vocabulary of 5th grade pupils’ at UPTD SD Negeri 078081Saombo school. The study employed a quantitative approach and a quasi-experimental one group a pre-test and a post-test design. The participants were 18 of 5th grade pupils selected through total sampling. Data were collected through vocabulary tests administered before the implementation of the Memory Card Game and afterward during three lessons. The data were analyzed using descriptive statistical methods and a paired t-test to assess the significance of the student’s vocabulary improvement. The results showed that the pupils’ mean score increased from 62.22 on the pre-test to 86.67 on the post-test, representing an improvement of 24.45 points. Statistical analysis revealed a significance level of 0.000, which was less than 0.05, and the calculated t-value was greater than the critical value. These results indicate that the Memory Card-game had a positive and significant effect on pupils’ English vocabulary. Therefore, the Memory card-game can be considered an effective and engaging learning tool for improving English vocabulary among primary school students.